Effect of ultrafine palm oil fuel ash and palm oil clinker on lightweight aggregate concrete - Hussein Mahmood, Hamada (2021)
The management of agricultural waste is one of the world’s environmental challenges due to accumulating large amounts of wastes in landfills causing the emission of carbon oxide. It is imperative to minimize the negative effect of the accumulation of these wastes. Numerous options have been tried by the cement and concrete technologists to solve such issues including the production of lightweight aggregate concrete ( LWAC) which required high cement content. Additionally, the statistical and mathematical models were generated to evaluate the performance of local wastes used in the LWAC production. Therefore, this study aims to investigate the effect of ultrafine palm oil fuel ash (UPOFA) as partial cement replacement and palm oil clinker (POC) as partial/full coarse aggregate replacement on the properties of lightweight aggregate concrete (LWAC). The UPOFA was used as partial replacement of cement from 0 to 30% and POC was used as coarse aggregate replacement from 0 to 100%. While, other concrete materials (water, fine aggregate, and super-plasticizer content) were kept constant in all concrete mixes. First, physical properties and chemical composition analysis were conducted on the UPOFA and POC to find out the suitability of using it as cement and coarse aggregate, respectively. Thereafter, the compressive strength, ultrasonic pulse velocity (UPV), flexural and tensile strength were conducted after 7, 28, 90, 180, and 365 days of curing. In addition to that, the test of SEM/EDX was investigated to show the effect of UPOFA and POC on the LWAC. In the response surface methodology (RSM), a set of statistical and mathematical techniques, was employed in 13 experimental runs to optimize the variable parameters. The optimum percentage of replacement levels of UPOFA and POC obtained from the experimental runs in central composite design (CCD) were analyzed using the analysis of variance (ANOVA). The novelty of this study is that it uses two palm oil wastes as the concrete materials in different percentages using RSM as a new statistical method for experimental design. The results obtained showed that the addition of UPOFA enhances the properties of the concrete specimens owing to the pozzolanic effect of siliceous nature of UPOFA especially at later curing age. On the other hand, POC has a highly porous nature and lower specific gravity than normal coarse aggregate which tended to lower the density and stiffness of the concrete. Incorporation of the UPOFA and POC achieved the lowest density of 1945 kg/m3 attributed to the lower specific gravity of UPOFA and POC than that of the cement and coarse aggregate. The highest slump value of 120 mm was achieved due to the usage of 30% UPOFA as cement replacement. The highest strength of LWAC was achieved at 365- days i.e. 85 MPa. This resulted in UPV, flexural, and splitting tensile strength values of 4375 m/s , 8.53 MPa, and 5.38 MPa, respectively. Analysis of the results by ANOVA indicated that the POC is more effective in terms of reducing the density, workability, compressive strength, UPV, flexural and tensile strengths, and enhancing the water absorption. While the UPOFA contributed to improving all the responses, the optimization results revealed that 12.42 % UPOFA as cement replacement and 11.27 % POC as coarse aggregate are optimum dosages to achieve the desirability’ value of 0.619. These levels correspond to the optimum values of density, workability, compressive strength, UPV, flexural strength, tensile strength, and water absorption as 2300.36 kg/m3, 97.98 mm, 78.87 MPa, 4079.34 m/s, 7.34 MPa, 5.36 MPa, and 1.72 %, respectively.